ISSUES OF IMPLEMENTATION OF INTERNATIONAL FINANCIAL REPORTING STANDARDS - Sheraliev Xayrulla , Karimovich (THE INNOVATION ECONOMY, 2025)
given the rich economic, natural and labor resource potential of the Republic of Uzbekistan now, with the right direction of investment policy, great success can be achieved. This will require retraining of accounting statements of enterprises based on IFRS (international Financial Reporting Standards). Today, accounting statements prepared by enterprises based on IFRS (national Accounting standards) include all elements of reporting prepared in accordance with IFRS. A significant difference between these reports will be related to the main characteristics of the value of financial and non-financial instruments.